-4=(-4x-5)

Simple and best practice solution for -4=(-4x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=(-4x-5) equation:


Simplifying
-4 = (-4x + -5)

Reorder the terms:
-4 = (-5 + -4x)

Remove parenthesis around (-5 + -4x)
-4 = -5 + -4x

Solving
-4 = -5 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-4 + 4x = -5 + -4x + 4x

Combine like terms: -4x + 4x = 0
-4 + 4x = -5 + 0
-4 + 4x = -5

Add '4' to each side of the equation.
-4 + 4 + 4x = -5 + 4

Combine like terms: -4 + 4 = 0
0 + 4x = -5 + 4
4x = -5 + 4

Combine like terms: -5 + 4 = -1
4x = -1

Divide each side by '4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| 7-4x=-33 | | .07(4x+10+5.30)=1.08(4x+5+8.60) | | 6c+15-5c-8= | | 2(n-3)=-2+2n | | 6=-5+r/8 | | 1.8+7n=9.5-3n | | 47=7d | | x=3y-111 | | 152/4=532/x | | 12(x-7)= | | 1.07(4x+10)+5.30=1.08(4x+5)+8.60 | | 1+0.07(4x+10)+5.30=1+0.08(4x+5)+8.60 | | 229/4=57.25 | | 7v+3+3v+4= | | 6x-(3x-4)=9x+22 | | x/3-13=12 | | 1+0.07(4x+10+5.30)=1+0.08(4x+5+8.60) | | 1/0.19=12/n | | -6+6x=-36+9x | | 3(r-6)=2(r+4) | | x^2+11=4x | | 23+8=j | | -1=(x+1) | | -12x-208=56-x | | w/6-2=5 | | 1/2x160 | | 1/4x160 | | -38-x=-2+5(-3x+4) | | 7+x/=9 | | 4z-z+vz+1+1+2z= | | 17=n-8 | | -8/6x=24 |

Equations solver categories